(untitled) (World Bulletin of Public Health, 2022)
Chamomile is a well-known medicinal plant. Ancient medicine believed that ingestion of chamomile broth opens blockages of the body, strengthens the brain, nerves, increases libido, is an antidote to all poisons, drives sweat, milk, urine, menstruation, stops the development of a runny nose, treats eye diseases and ear winds. Chamomile decoction treats suffocation, jaundice, fatigue, liver pain, abdominal pain, anus, uterus, dissolves tumors in these organs. Chamomile cleanses the body of harmful matter, treats mucous and bile fever. If you sit in a bath of chamomile decoction, the fetus will drive out, menstruation, crush kidney stones. In the form of a bandage, chamomile flowers treat skin itching, lacrimation. If chewing chamomile flowers is useful for inflammation of the oral mucosa. Chamomile flower powder, when injected into the eyes, treats their diseases